(untitled) (Global Journal of Management and Business Research, 2014)
This paper examines the effect of inflation and economic growth on unemployment in Sri Lanka for the period 1990-2012. To achieve this objective, secondary data has been taken from Central Bank annual reports for the above period. To test unit root or stationary, Augmented Dickey Fuller Test was used. In addition to that, ordinary least square technique and to determine the causality among the above variables Granger Causality test also were applied. Results of the unit root test indicate that only Gross Domestic Product (GDP) has stationary and unemployment and inflation have unit root problem or non-stationary at level. But when these two variables are tested at first difference then the problem of unit root has disappeared and hence they have become stationary at first difference.